2015
DOI: 10.1177/0194599815596494
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Velopharyngeal Insufficiency Postadenotonsillectomy

Abstract: Our data are consistent with the literature that most VPI after adenotonsillectomy is temporary in nature and resolves by 5 months postoperatively. Combined procedures were shown to have a significantly higher risk of VPI. Our rates of VPI were much higher than that previously cited and may be indicative of subclinical cases of VPI, which were accounted for due to this study's unique methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…It often manifests as hypernasality, poor speech output, and nasal regurgitation. Unlike VPI due to anatomical abnormalities such as cleft palate, VPI following adenoidectomy is usually transient and resolves without further surgical intervention [53]. Cephalometry may be a useful way of providing information on VPI, as it can help indicate which children have VPI, and postoperatively which children will have prolonged postoperative VPI [54,55].…”
Section: Adenoidectomy Complicationsmentioning
confidence: 99%
“…It often manifests as hypernasality, poor speech output, and nasal regurgitation. Unlike VPI due to anatomical abnormalities such as cleft palate, VPI following adenoidectomy is usually transient and resolves without further surgical intervention [53]. Cephalometry may be a useful way of providing information on VPI, as it can help indicate which children have VPI, and postoperatively which children will have prolonged postoperative VPI [54,55].…”
Section: Adenoidectomy Complicationsmentioning
confidence: 99%
“…10,11 Velopharyngeal insufficiency (VPI) has been reported to occur in up to 13.6% of patients after T&A at a 3-week postoperative visit. 12 Most resolve with time and/or speech therapy at 5 months; however, approximately half of those with early VPI after T&A will have persistent VPI requiring surgical intervention. [11][12][13] Because of the hypotonia associated with both PW and T21, these children may be at higher risk of having postoperative VPI.…”
Section: Introductionmentioning
confidence: 99%
“…12 Most resolve with time and/or speech therapy at 5 months; however, approximately half of those with early VPI after T&A will have persistent VPI requiring surgical intervention. [11][12][13] Because of the hypotonia associated with both PW and T21, these children may be at higher risk of having postoperative VPI. One study has assessed VPI after T&A in PW patients and found that 2 of their 11 patients required surgical intervention for their postoperative VPI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all patients underwent adenoidectomy along with tonsillectomy. Velopharyngeal insufficiency may also be encountered after tonsillectomy alone, but it is more common in the pediatric population because tonsillectomy is generally performed along with adenoidectomy in children [ 14 ]. Consistently, no patient experienced a velopharyngeal insufficiency in our adult population.…”
Section: Discussionmentioning
confidence: 99%